Expanding role of absolute zero fluoroscopy atrial septal defect closure: a single-center experience - Prakoso, Radityo; Ariani, Rina; Kurniawati, Yovi; Siagian, Sisca Natalia; Sembiring, Aditya Agita; Sakti, Damba Dwisepto Aulia; Kuncoro, B. R. M. Ario Soeryo; Mendel, Brian; Rudiktyo, Estu; Soesanto, Amiliana Mardiani; Lelya, Olfi; Lilyasari, Oktavia (Frontiers in Cardiovascular Medicine, 2025)
IntroductionZero-fluoroscopy, exclusively ultrasound-guided atrial septal defect (ASD) catheter closure has been reported. However, data on the effectiveness of this technique in complex cases remains limited.ObjectivesThis study aims to evaluate the safety, efficacy, and outcomes of ASD catheter closure using exclusive ultrasound guidance, with a particular focus on complex cases.MethodsWe conducted a retrospective review of clinical data from patients who underwent attempted ASD catheter closure with exclusive ultrasound guidance at our institution between July 2018 and April 2024. Patients were categorized into two groups based on the complexity of their cases (simple vs. complex ASD cases). Complex cases included patients with large defects (≥25 mm), multiple or fenestrated ASDs, deficient posterior-inferior rim <3 mm, deficient retro-aortic rim <5 mm, pulmonary hypertension, septal malalignment, and pregnancy. We analyzed and compared demographic information, procedural data, and outcomes between the two groups.ResultsWe identified 339 patients (18.2% males, 53.6% adults) with a median age of 21 years (IQR, 9–38) and median weight of 46.5 Kg (IQR, 22–59). Overall, median defect size was 20 mm (IQR, 16–25) and device size was 26 mm (IQR, 20–32). 248 (73.1%) patients were classified as complex including 98 (28.9%) with large defects (≥25 mm), 33 (9.7%) with multiple or fenestrated ASDs, 53 (15.6%) with pulmonary hypertension, 171 (50.4%) with rim deficiency, 50 (14.7%) with septal malalignment, and 6 (1.7%) with pregnancy. Two procedures (0.5%) were guided using transthoracic ultrasound and 337 (99.4%) using both transthoracic and transoesophageal ultrasound. The implantation success rate was 98.9% in simple cases and 97.1% in complex cases (p < 0.001). The rate of conversion to fluoroscopy guidance was 0 (0%) in simple cases and 7 (2.8%) in complex cases (p < 0.001). The median procedural time was 41 min (IQR, 30–47) in simple cases and 45 min (IQR, 36–62) in complex cases (p = 0.008). Sixteen patients (4.7%) underwent balloon-assisted procedures, and 12 (3.5%) required redeployment. There were 6 (1.7%) serious procedural complications (0 in simple cases, 6 in complex cases). The median follow-up was 187 days (IQR, 21–428.7). There were no residual shunt at latest follow-up for both simple and complex cases.ConclusionsZero-fluoroscopy exclusively echocardiography-guided ASD closure is effective in both simple and complex cases. However, the rate of conversion to fluoroscopy and implantation failure are significantly higher in complex ASD cases.